A new blind snake (Typhlopidae) from Northeastern Cuba - Domínguez, Michel; G., Ansel Fong; Iturriaga, Manuel (Zootaxa, 2013)
Typhlops leptolepis sp. nov. is a new blind snake from Holguín Province, northeastern region of Cuba. The new species is characterized by its small and thin body size, as well as a narrow rostral in dorsal view, longer than broad, with parallel to curved sides, tapering toward anterior tip. The preocular is in contact with third supralabial only. It has 20 anterior scale rows reducing to 18 posteriorly at around midbody or posterior to midbody, moderate to high middorsal scale counts (250– 308), and a peculiar coloration (head, neck, and tail whitish spotted in ventral view). Based on its morphology, the new species can be placed within the Typhlops lumbricalis species group and a key to the species belonging to this group is presented.